The Completeness of Filling Out Medical Record Documents and the Accuracy of Codes at Reksodiwiryo Hospital - Wahyuni, Annisa; Oktavia, Dewi; Lukmanita, Zara Anida (RRZ Scientific Publishing, 2024)
A hospital is an institution whose primary function is to provide health services to the community. One of the government's efforts to provide health services to the community is implementing the National Health Insurance Program (JKN), which the Social Security Program Organizing Agency organizes in the health sector. This research analyzed the factors associated with delays in BPJS claims at Dr. Hospital. Reksodiwiryo Padang. This research was a descriptive quantitative study with a cross-sectional study design. The research showed that six medical record files (6.5%) had inaccurate codes, while 86 (93.5%) used the correct ones. In addition, 91 files (98.9%) of inpatient medical records needed to be completed, and only one file (1.1%) was completed. Inaccuracy in diagnostic coding affects delays in submitting claims at Dr. Hospital. Reksodiwiryo Padang. It is hoped that officers can understand the coding rules based on ICD-10 for diagnoses and ICD-9 CM for actions or procedures to guarantee the quality of service at the hospital.